PENGARUH ANCAMAN COVID-19 YANG DIRASAKAN TERHADAP KEPUASAN KERJA PADA KARYAWAN HAMMER DI JAKARTA - Retno Dwi Jayanti; Netania Emilisa; Evi Robiana (Jurnal MANAJERIAL, 2023)
Perceptions of perceived covid-19 threat and job stress can affect job satisfaction and counterproductive work behavior among employees, therefore this study aims to examine the effect of the perceived covid-19 threat, job stress, job satisfaction on counterproductive work behavior among Hammer employees in Jakarta. Respondents from this study used a total sample of 167 respondents who worked at the Hammer Jakarta showroom. Sampling in this study used a non-probability sampling method with a purposive sampling approach. Whereas in testing the hypothesis using an analysis tool in the form of a Structural Equation Model (SEM). The results of testing the hypothesis in this study indicate that the perceived covid-19 threat has a positive effect on job stress, job stress has a negative effect on job satisfaction, job stress has a positive effect on counterproductive work behavior, job satisfaction has a negative effect on counterproductive work behavior. The implications for HR managers are that they are expected to always pay attention to the working environment conditions within the company, pay attention to the perceived covid-19 threat and job stress on employees, increase job satisfaction and prevent counterproductive work behavior.